2012
DOI: 10.1016/j.ijscr.2012.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Gorlin syndrome and bilateral ovarian fibroma

Abstract: Gorlin-Goltz syndrome is a hereditary pathology that includes numerous clinical manifestations. Diagnosis is clinical and genetic confirmation is unnecessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In the general population, ovarian fibromas represent 5% to 6% of ovarian neoplasms; they are unilateral in 90% of the cases and are rarely calcified [7]. They commonly affect women of reproductive age, although sporadic cases in young premenarchal women have been reported, both in association with GS and otherwise [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, ovarian fibromas represent 5% to 6% of ovarian neoplasms; they are unilateral in 90% of the cases and are rarely calcified [7]. They commonly affect women of reproductive age, although sporadic cases in young premenarchal women have been reported, both in association with GS and otherwise [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…10 Gorlin syndrome, also called nevoid basal cell carcinoma syndrome or basal cell nevus syndrome, is a rare hereditary disease and it is inherited in an autosomal dominant manner. 11 It affects multiple organ systems of the human body and is associated with an increased risk of developing several types of benign and malignant tumors. 11 This syndrome is caused by a germline mutation in the human homolog of the patched (PTCH1) gene, which is located on chromosome 9.…”
Section: Pure Stromal Tumors Fibromasmentioning
confidence: 99%
“…Among these criteria, the proportion of women aged 16 -45 years with an ovarian fibroma ranged from 12.5% to 17.0% [7] [9]. Some surgical cases of Gorlin-Goltz syndrome with an ovarian tumor have been reported [10] [11]. One study reported the use of conservative treatment for recurrent ovarian fibromas in a 22-year-old patient with Gorlin-Goltz syndrome [10], and the other described a case of Gorlin-Goltz syndrome complicated with hydronephrosis due to a huge ovarian tumor [11].…”
Section: Introductionmentioning
confidence: 99%
“…Some surgical cases of Gorlin-Goltz syndrome with an ovarian tumor have been reported [10] [11]. One study reported the use of conservative treatment for recurrent ovarian fibromas in a 22-year-old patient with Gorlin-Goltz syndrome [10], and the other described a case of Gorlin-Goltz syndrome complicated with hydronephrosis due to a huge ovarian tumor [11]. However, no studies have mentioned subsequent fertility preservation by using oocyte cryopreservation process.…”
Section: Introductionmentioning
confidence: 99%